GEODATABASE ON THE EXAMPLE OF THE CADASTRE OF VINEYARDS - Ema Dizdarević; Mirko Borisov; Mirko Petrović; Ivan Stoilković; Nenad Rakičević (Geodetski Glasnik, 2022)
This paper describes the creation of the geodatabase of the vineyard cadastre. In order to create the database itself, it was necessary to make a selection of what data is suitable to collect, in what way, and also to determine what existing data is. Due to the sheer size of the vineyards on Ćemovsko polje, such records are necessary. The focus of this work is on the collection, processing of data, and the formation of a functional georeferenced database. The goal of creating such a database is to facilitate the search, addition of data, and manipulation of the same, as well as transparency of the tables for the needs of further processing of grapes and obtaining final products from the Plantation 13th July, located on Ćemovsko polje in the vicinity of Podgorica, Montenegro.